Design of the Educational Video “Creative Survival Guide” to Help Gen Z Workers Cope with Culture Shock in the Creative Agency Industry in Medan - Jeje Hopetian Sembiring; Jolyne Tiodora; Rizkika Utami; ⁠Rizka Alya Triztika (Sean Institute, 2026)
The rapid growth of the creative agency industry in Medan has not been matched by structured working systems, creating a significant gap between academic life and the professional world that Generation Z workers are forced to navigate upon entry. This study addresses the phenomenon of culture shock experienced by Gen Z workers entering creative agencies in Medan, encompassing the clash between expectations of flexible and appreciative workplaces and the reality of unpredictable workloads, unrealistic deadlines, inadequate compensation, and insufficient institutional mental health support, which consequences that extend beyond psychological distress to tangible physical health disruptions. A qualitative descriptive analytical approach was employed, with data collected through semi structured in depth interviews with three creative workers possessing 1–3 years of experience, and subsequently analyzed using narrative analysis to understand how each individual constructs meaning from their adaptation process. Based on these findings, an approximately 13 minutes educational video was produced in a cinematic documentary format across three narrative segments, presented not as an instructional guide but as an authentic representation of lived experience designed to help Gen Z audiences feel understood, psychologically prepared, and capable of establishing healthy professional boundaries before entering the creative agency world.